SANSKRIT LANGUAGE IS THE MEDIUM OF INNOVATION IN MUSIC: संगीत में नवाचार का माध्यम संस्कृत भाषा - Sharma, Manisha (International Journal of Research -GRANTHAALAYAH, 2015)
Along with human civilization, arts have developed. Until the last period of the Vedic era no independent texts related to music are available, however, references to music art are definitely found at the place. In the Rigveda, many references are found in connection with the three songs, instruments and dances. In the Rigveda, words like Geer, Gatu, Gatha, Gayatra and Geeti were used for the song. These were all contemporary song types and had the basis of verses and singing style. For the song and its tune, it was also the name 'Sama'. Sama has been a synonym for Dhun or Swaravali. These were fumes sung under erstwhile public music. Vedic mantras were sung on the lines of these. Music was suitable for both Lokaranjan and Ishwar Ranjan, such was the belief of Vedic Aryans. Singing of mantras was considered more effective than simple recitation or recitation of mantras on the occasion of Yajna. In ancient music both words and vowels were considered to be of equal importance. Vedic hymns began to be sung, as words were required to sing the song. In ancient music, the importance of both word and tone was considered. This alliance of vowels and words was called 'Sama'. मानव सभ्यता के साथ-साथ कलाओं का विकास हुआ है । वैदिक युग के अंतिम कालखण्ड तक संगीत संबंधी कोई स्वतंत्र ग्रंथ उपलब्ध नहीं है तथापि संगीत कला के संबंध में उल्लेख स्थान पर अवश्य प्राप्त होते हैं । ऋग्वेद में गीत, वाद्य और नृत्य तीनों के संबंध में अनेक उल्लेख पाये जाते हैं। ऋग्वेद में गीत के लिए गीर, गातु, गाथा, गायत्र तथा गीति जैसे शब्दों का प्रयोग किया जाता था । यह सभी तत्कालीन गीत प्रकार थे और इनका आधार छन्द और गायन शैली थी । गीत तथा उसकी धुन के लिए ‘साम‘ संज्ञा भी रही । साम धुन या स्वरावली के लिए पर्यायवाची शब्द रहा है। यह तत्कालीन जनसंगीत के अंतर्गत गायी जाने वाली धुनेें थीं । इन्हीं के तर्ज पर वैदिक मन्त्र गाये जाते थे । संगीत लोकरंजन तथा ईश्वर रंजन दोनों के लिए उपयुक्त है, ऐसी वैदिक आर्यों की धारणा थी । यज्ञ के अवसर पर मंत्रों के साधारण पाठ या पठन की अपेक्षा मंत्रों का गायन अधिक प्रभावशाली माना जाता था । प्राचीन संगीत में शब्द और स्वर दोनों का समान महत्व माना जाता था। गीत गाने के लिए शब्दों की आवश्यकता होती है, इस रूप में वैदिक ऋचाएँ गाई जाने लगी। प्राचीन संगीत में शब्द और स्वर दोनों का महत्व माना जाता था । स्वर तथा शब्द का यही गठबन्धन ‘साम‘ कहलाता था ।